Experimental and numerical study on direct electrical heating for plug removal of subsea waxy crude pipelines. (November 2019) - Yao, Z.X.; Li, J.X.; Wang, K.; Song, Y.N.; Li, X.
Highlights: A numerical model of wax plug melting by Direct Electrical Heating is proved valid. The temperature of pipe wall is higher at top because of the natural convection. The melting rate decreases when the liquid fraction rises to about 0.9. Correlations are developed which may provide reference for practical engineering. Heating with the total power under the maximum safe power is the most economical. Abstract: Subsea pipeline of waxy crude oil may face a high risk of the wax plug during shut down or pigging. Direct Electrical Heating (DEH) technology is expected to be an efficient and convenient way to melt the wax plug in the subsea pipeline. An industrial-scale experimental facility with a test tube of 10-in. diameter and a power supply of 0–1350 A is set up, and then several sets of experiments are carried out. Simultaneously, the melting process of the wax plug is simulated by FLUENT software. The numerical model is validated from the aspects of liquid fraction and solid patterns. The melting rate and temperature of the wax plug with different wax content and current are analyzed, and the temperature of the pipe wall is considered for the sake of pipeline integrity. Furthermore, to avoid secondary solidification, the recooling process of the wax plug and pipe wall is also discussed. Finally, the effects of the "Maximum Allowable Temperature", "Maximum Safe Power", "Effective Liquid Fraction" and "Applicable Heating Time" on economic evaluation are investigated, and the correlations are developed between the above factors and common pipe diameters (6–32-in.), which shows heating with maximum safe power is also the most economical method in engineering.